2014
DOI: 10.1159/000368086
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasonography May Provide an Indirect Estimation of Lung Porosity and Airspace Geometry

Abstract: Background: Echographic vertical artifacts (B-lines) in chest ultrasonography have often been associated with pathological patterns. A scientifically sound explanation of these artifacts has not yet been proposed. Objectives: The ‘spongy' nature of the lung in its liquid and solid components and the changes that take place in peripheral airspace (PAS) geometry might be the key point to understanding these phenomena. Methods: Six excised right rabbit lungs were obtained. Each lung underwent direct ultrasound ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 39 publications
2
99
0
1
Order By: Relevance
“…Soldati et al [20] considered the 'spongy' nature of the lung in its liquid and solid components and the changes that take place in peripheral airspace geometry, which might be the key to understanding these phenomena. From animal experiments, they concluded that airspace geometry, frothy nature and porosity are the determinants of the different behaviour of ultrasound wave interactions with the sub pleural lung parenchyma.…”
Section: Lung Artefactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soldati et al [20] considered the 'spongy' nature of the lung in its liquid and solid components and the changes that take place in peripheral airspace geometry, which might be the key to understanding these phenomena. From animal experiments, they concluded that airspace geometry, frothy nature and porosity are the determinants of the different behaviour of ultrasound wave interactions with the sub pleural lung parenchyma.…”
Section: Lung Artefactsmentioning
confidence: 99%
“…From animal experiments, they concluded that airspace geometry, frothy nature and porosity are the determinants of the different behaviour of ultrasound wave interactions with the sub pleural lung parenchyma. Chest ultrasound may be interpreted as an indirect 'estimator' of lung porosity [20].…”
Section: Lung Artefactsmentioning
confidence: 99%
“…Aside from the validity of the above-stated comments by Soldati et al [1], we would respectfully like to ask the authors for some clarification to reinforce their message:…”
mentioning
confidence: 96%
“…We appreciate the insight provided by Soldati et al [1], who addressed the origin of artifacts in thoracic ultrasound (US), stating that they do not correspond to anatomical structures, visible or otherwise [1]. Indeed, like noise and interference, artifacts ‘detected' by biomedical signaling tools, being equipment- or technique-related errors in the perception or representation of visual or auditory data [2], can be minimized and removed by clinical recording.…”
mentioning
confidence: 99%
See 1 more Smart Citation